Ornamental Fish Farming a Tool to Empower Rural Women of West Bengal, India - Sinha, Archana; Swain, Himanshu S; Das, B K (Journal of the Inland Fisheries Society of India, 2020)
Ornamental fish farming is an emerging business for rural women of West Bengal, India. About 20 to 30 thousand women fishers are involved in thistrade. Ornamental fish production centres are set up at Howrah, South 24 Parganas, Uttar Dinajpur, Malda etc under the Government assistance. They are engaged in the production and marketing of ornamental fishes andmanagement of freshwater aquaria as natural nurturers. In addition to fish breeding, they have also developed the skill to prepare on farm feed, treat diseased fish, caring the young ones etc. Women have even taken over the marketing network from men. At some hatcheries, it is the women who squat by the tanks, painstakingly scooping out the stronger fish, packingthem into poly bags. They have demanded the setting up of local markets to bypass the middlemen. The average income of each member of a Self Help Group (SHG), involved in ornamental fish trade, ranged from Rs. 3000--4500/month. A system of accreditation/ registration of production facilities, aquarium traders and service providers is the attention of the policy makers of the country.Key words : Ornamental fish, Gender issues. Alternate livelihood, Socioeconomics